A comparative study of Geomagnetic and Ionospheric changes at Kodaikanal and Huancayo - SIVARAMAKRISHNAN, M.V. (MAUSAM, 1956)
A study of geomagnetic field variations for five years, 1949 to 1953, and ionospheric changes during 1952-1954 at Kodaikanal reveals that Kodaikanal, situated year the geomagnetic equator shows more or less the same anomalous behaviour as Huancayo, The sudy shows. The abnormal, large range in the horizontal intensity H during quiet days,(ii) No abnormality in H during geomagnetic disturbances, (iii) Amplitudes of S.C.’s during noon are greater near the geomagnetic equator than at stations further away from it (iv) A midday decrease of foF2 on quiet days (the bite-out effect), (v) Increase in the electron density of F2 layer with increase in geomagnetic activity conductive to better conditions for radio propagation, and (vi) Occurrence of the lunar stratification of the F2 layer and its disappearance at the lunar times 0700 and 1930 hours.